Host-substrate preference of Theocolax elegans (Westwood) (Hymenoptera: Pteromalidae), a larval parasitoid of the maize weevil, Sitophilus zeamais (Motschulsky) (Coleoptera: Curculionidae) - Sitthichaiyakul, Saruta; Amornsak, Weerawan (Agriculture and Natural Resources, 2017)
The solitary parasitoid Theocolax elegans (Westwood) (Hymenoptera: Pteromalidae) was investigated attacking larvae of the maize weevil, Sitophilus zeamais (Motschulsky) (Coleoptera: Curculionidae) under laboratory conditions. T. elegans parasitoids were mass reared on 21-day-old S. zeamais fed with different host substrates consisting of brown rice, maize, sorghum and wheat. The developmental time of S. zeamais was observed. The widest head capsule was recorded from S. zeamais developing in brown rice grain kernels. The head capsule width was used to determine the age of the larval instars. The sex ratio of T. elegans progeny emerging from brown rice was the same in the choice and no-choice tests (1.8:1.0 and 1.8:1.0, respectively). Female parasitoids preferred to oviposit on S. zeamais developed in brown rice grain kernels in both tests. The number of parasitoid progeny emerging from different host substrates was different in the choice and no-choice tests. The progeny of T. elegans females and males were fully winged, short winged and wingless.